EGFR Tyrosine Kinase Inhibitor Efficacy in Older Adult Patients with Advanced EGFR-Mutated Non-Small-Cell Lung Cancer: A Meta-Analysis and Systematic Review - Chang-Hung Chen; Deng-Wei Chou; Kuo-Mou Chung; Han-Yu Chang (Medicina, 2022)
Background and Objectives: Lung cancer remains the most common malignancy worldwide. As the global population ages, the prevalence of epidermal growth factor receptor (EGFR)-mutation-positive non-small cell lung cancer (NSCLC) is increasing. Materials and Methods: We performed a meta-analysis and a systematic review of randomized, controlled trials to evaluate the efficacy of EGFR TKIs on progression-free survival (PFS) and overall survival (OS) in older adult patients with advanced EGFR-mutated NSCLC. A total of 1327 patients were included; among these, 662 patients were >65 years of age. Results: A pooled analysis indicated (1) an overall improvement in higher PFS for dacomitinib and osimetinib than that for other drugs (hazard ratio [HR] = 0.654, 95% CI: 0.474 to 0.903; p = 0.01) and (2) and no significant difference in the OS between the EGFR TKIs (HR = 0.989, 95% CI: 0.796 to 1.229; p = 921). Conclusion: Our study found that osimertinib achieved a higher PFS than all other EGFR TKIs did. Osimertinib is the preferred EGFR TKI for treatment of older adult patients with advanced EGFR-mutated NSCLC.